The Effectiveness of Splints in Temporomandibular Joint Disorders - Nashwah Hinaz, Pradeep D2 , Ashok V3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
TMD is defined as a muscular and articular disorder. The primary goal in the treatment of temporomandibularjoint disorder is to ease pain or mandibular dysfunction with Conservative treatments such as splint therapy,and manipulation. occlusal splint insertion and physical treatment are the most commonly used conservativealternatives through which approximately 90% of all TMD cases can be successfully treated. The aim of thestudy was to assess the effectiveness of splints in temporomandibular joint disorders. Sample was collectedfrom June 2019 to March 2020 from Saveetha Dental College and Hospitals, Chennai. Data collected istabulated in Excel and statistical analysis using SPSS is done to obtain results. Out of 61 patients, 59%were male and 45.9% were female. The mean age of the participants is 33.21 years. Within the limitationsof the study, it was concluded that splint therapy was effective for 59.02% patients with temporomandibularjoint disorder patients. Also, splint therapy was more effective in males (32.79%) as compared to females(26.23%).